Adult male perceptions on the implementation of the safe male circumcision communication strategy (2009-2012) in Gaborone Botswana - Setumo, Samson (My University, 2016)
Introduction Botswana has been hard hit by HIV with an adult prevalence rate at around 19.03% (Statistics Botswana, 2013a). Over the years many interventions have been put in place to curb the scourge without any meaningful success. In response to three randomized controlled trials which found that male circumcision reduced the risk of getting an HIV infection by up to 60%, in 2008 Botswana introduced the Botswana National Safe Male Circumcision (BNSMC) Strategy to aggressively scale up male circumcision in Botswana (Ministry of Health, 2008). However, when the strategy, was evaluated, male circumcision had only increased by a mere 13.3% in four years, instead of the anticipated 80% (Ministry of Health, 2008, Statistics Botswana, 2013a). The aim of this study therefore was to explore adult male perceptions of the implementation of the BNSMC strategy in Gaborone, Botswana, with an aim to inform future campaigns. Methods An exploratory qualitative cross-sectional study design was used and data were collected through In-depth Interviews (IDIs) and Focus Group Discussions (FGDs). A total of 22 (circumcised and uncircumcised) men between the ages of 18 to 49 residing in and around Gaborone, participated in IDIs (10) or FGDs (2). Participants were recruited through purposive and snowball sampling. All interviews were audio recorded and transcribed. A combination of deductive and inductive thematic analysis of the transcripts was conducted. Results What emerged strongly is the role played by society, friends and relatives in influencing the individual to circumcise, beyond formal campaign messages. In particular peer influence seemed to have played a crucial role. The study has identified multiple types of fear as key barriers to SMC, including fear of erectile dysfunction, fear of pain, fear of HIV testing and other fears related to adverse effects such excessive bleeding and complications with the procedure. Participants also expressed lack of trust in the health system which they attributed to incidents which occur at health facilities. Study participants did not think that the TV and radio broadcasters used for the campaign were effective. Although most participants felt that edutainment was relatively effective because it engaged people at an emotional level and is liked by the youth, nobody describe it as influencing their own decision and some discredited using music because people do not listen to the embedded messages. On the other hand, the use of a musician celebrity to promote SMC reportedly influenced some to circumcise. Conclusions Data from this study has shown that intended SMC key messages had limited reach and were insufficient on their own to increase SMC. Building on the use of celebrities, more could be done in the future to include other influential people, such as girlfriends and peers. Formative research is indicated to identify more appropriate mass media broadcasters for intended audiences and to explore additional channels. The content of messages must also be reviewed in light of what audiences say influences their decisions. In particular, the fear of testing and lack of trust in the health care services may have negatively affected the SMC up-take outcome more than implementers think. Going forward, evidence based planning of future interventions could address some of the identified gaps through the use of social and behavior change communication theories as the basis for program design, implementation and evaluation.
A research report submitted to the Faculty of Health Sciences (School of Public Health), University of the Witwatersrand, in Partial Fulfillment of the Requirements for the Degree of Masters in Public Health in the field of Social and Behavior Change Communication Date: 26 June, 2015